Nonsurgical Endodontic Treatment of a Maxillary Central Incisor with Two Separate Roots: A Case Report - Nabavizadeh, Mohammad Reza; Jouyandeh, Mohammad Reza; Atbaee, Adnan; Sedigh Shams, Mahdi (Iranian Endodontic Journal, 2010)
The success of endodontic therapy requires knowledge of the internal and external dental anatomy and its variations in presentation. This case report involves endodontic treatment of a traumatized maxillary central incisor with two separate roots.